Correction: Multilocus Sequence Typing as a Replacement for Serotyping in Salmonella enterica. - Mark Achtman; John Wain; François-Xavier Weill; Satheesh Nair; Zhemin Zhou; Vartul Sangal; Mary G Krauland; James L Hale; Heather Harbottle; Alexandra Uesbeck; Gordon Dougan; Lee H Harrison; et al. (PLoS Pathogens, 2020)
[This corrects the article DOI: 10.1371/journal.ppat.1002776.].